The Potential of Crop Residues as Feed Resources for Ruminant in Indonesia - Jasmal A Syamsu; Lily A Sofyan; K Mudikdjo; E Gumbira Sa’id (Indonesian Center for Animal Research and Development, 2003)
The growth rate of ruminant population between 1997-2001 was decreased for beef cattle 1,46%, buffalo 6,73%, goat 2,89% and sheep 0,55%. But the population of dairy cattle increased 2,90%, meanwhile milk production increased was 6,29% per year. On the other hand, at the same time the number of slaughtered animals increased for beef cattle (0,53%), goat (4,39%) and sheep (23,15%), and buffalo was decreased 2,13%. Production of ruminant meat decreased 2,39% annually. The goat meat was decreased (9,03%) than sheep meat (6,36%), buffalo meat (2,51%) and beef meat (0,95%). The quantity of crop residues produced as a feed resources for ruminant is 51.546.29751.546.297 ,3 tons dry matter or 23.151.344,6 tons total digestible nutrient., as result it available feed for ruminant was 14.750.777,1 animal unit (AU). While the population of ruminant is 11.995.340 LU so that it can be able to increase the population up to 2.755.437,1 LU or 18,68 %. Key words: Crop residues, ruminantCallSend SMSAdd to SkypeYou'll need Skype CreditFree via Skype